Features of the pathomorphological structure of the aterosclerotic plaques of carotid aterosclerosis - Yu. I. Kuzyk (Zaporozhye State Medical University, 2019)
Carotid arteriosclerosis is a recognized leader among causes of ischemic disorders of the cerebral circulation. It is known that brain infarction occurs with atherosclerotic stenosis and thrombosis of the carotid arteries in approximately 40 % of cases. The peculiar geometry of carotid bifurcation creates conditions for the development of atherosclerotic plaques. The aim of the work is determination of pathomorphological features of the structure of atherosclerotic plaques in carotid atherosclerosis. Materials and methods. Histological, histochemical and immunohistochemical studies of surgical material in 680 patients were performed. Results. On the basis of pathomorphological analysis of the plaque in carotid AS they can be divided into complicated and uncomplicated. The first type is atheromatous unstable plaques with the prevalence of foci of atheromatosis, lympho-macrophage infiltration, intraplaque hemorrhage, necrosis of fibrous elements and edema. Immunohistochemically they are characterized by high expression of MMP-9 in macrophages and lymphocytes with degradation of type I collagen in the surface and deep layers of the plaque coating and its replacement by type III collagen (P < 0.05). The second type of plaque is stable uncomplicated with the advantage of fibrosis, hyalinosis and petrification. Immunohistochemical structure of plaques was collagen type I, expression of collagen type III was low, expression of MMP-9 was moderate (P < 0.05). Conclusions. High expression of MMP-9 in carotid atherosclerosis in macrophage-lymphocytic infiltrates in atheromatosis and neovascularization sites was found to result in degradation of type I collagen with its replacement by type III collagen. Such pathomorphological changes underlie plaque instability - the development of intraplaque hemorrhages, ulcers with embolic complications. Synthesis of collagen type I with low expression of type III collagen and MMP-9 has been found to determine the basis of the structure of fibro-muscular plaques. This ensures their hemodynamic stability and stable vascular stenosis.